O papel do estágio nas escolas estaduais de educação profissional do Ceará no contexto de crise estrutural do capital: formando jovens trabalhadores para o desemprego - Monteiro, Maria Clea Ferreira (2018)
The research considers, in its development, the labor-education relationship present in the activities of the compulsory traineeship offered in the curriculum of the State School of Professional Education (SSPE) of the State of Ceará. Its general objective is to analyze, focused on the marxist criticism, the formation of the students in the SSPE of Ceará, searching out especially the place and role of the supervised internship in the process of qualifying young workers. In a specific way, it seeks, besides other purposes: i) To problematize the work-education relationship put in the stages of the State School of Professional Education in the context of the structural crisis in the capital; ii) Analyze the training of skilled and cheap labor, through the educational guidelines aimed at the education of poor countries aligned with the dissemination of the theoretical principles of the new educational paradigms, focusing on the discourse of training for work; iii) Establish a relationship between the SSPE, which hold the ideological expression that promotes the employability discourse, in disagreement with the growing structural unemployment; iv) to understand the relation between the internship of professional schools and the fulfillment of the needs imposed by the labor market. Thus, the presumption is that the curricular stage of vocational education, under the influence of practice, empties the training of the worker, focusing on purely instrumental aspects, under the justification of forming a workforce supposedly qualified as a reflection of the impositions of expanded reproduction of capital. The research is based on the ontological conception of Marx, considering the centrality of work in the self-construction of man, explicitly categorizing work as a foundational category of the world of men. Thus, we chose to use the Marxian ontology, later rescued by Lukács, in order to unveil what the thing is in its essence, seeking the origin, development and social function of the object, without losing the category of social totality. It has been found that educational policies geared to professional education, generally, show themselves as preparation for the labor market in order to meet the needs of capital in crisis.